Co-Treatment of EFF and 1-MCP for Enhancing the Shelf-Life and Aroma Volatile Compounds of Oriental Sweet Melons (Cucumis melo var. makuwa Makino) - Xiao-hang BAI; Lu-hua TENG; De-qing LÜ; Hong-yan QI (Journal of Integrative Agriculture, 2014)
Compared to other melon types, oriental sweet melon (Cucumis melo var. makuwa Makino) is quite a different species with a shorter shelf-life due to its typical climacteric behavior and thin pericarp. The purpose of this experiment is to explore the effects of co-treatment of enhanced freshness formulation (EFF) and 1-methylcyclopropene (1-MCP) on physiological changes and the content of aroma volatile compounds introduced by them of two oriental sweet melon cultivars (Yumeiren and Tianbao) during storage. The melons were stored in incubators with temperature of 15°C and a relative humidity of 85% for 24 d during which fruit quality and related physiological index were measured. Compared to the control, both treatments delayed fruit weight loss rate and kept the fruit firmness, water content and soluble solids content. Ascorbate peroxidase (APX) and phenylalanine ammonia lyase (PAL) activities showed fluctuations in treated melons, while lipoxygenase (LOX) activity (P<0.01) and malondialdehyde (MDA) content (P<0.05) decreased compared to control. During the early stage of storage, alcohols and aldehydes were the main volatile compounds, and esters gradually increased during storage. Of all the esters, acetic esters were the main components, followed by oxalic acid esters and other esters. The total content of aroma volatile compounds, esters, alcohols and aldehydes of co-treated melons were all higher than those of 1-MCP treated and control melons. In addition, the aroma volatile peak of co-treated melons occurred later than that of 1-MCP treated and control melons. In summary, co-treatment of EFF and 1-MCP was more beneficial than 1-MCP treatment to delay ripening and senescence, maintain fruit quality, enhance shelf-life and improve levels of aroma volatile compounds.